Factors affecting lower back pain among hospital healthcare workers in Kedah during covid-19 pandemic - Mohd Hashimi, Abas (2023)
Lower back pain (LBP) has become one of the most prevalent work-related syndromes of the twenty-first century and overall occupational safety risk. This study investigates the causes of LBP among healthcare workers who worked during the COVID-19 pandemic in 2020, when the healthcare system faced its most significant challenges. Physical job demand, psychological job demand, and social support as the factors are investigated. The hypotheses developed to examine the associations between the factors and LBP are tested based on the opinion of hospital healthcare workers in Kedah based on the three objectives of this research. To test the hypotheses, 171 responses to a self-administered questionnaire are collected. The collected data is analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Physical job demand and psychological job demand were found no have significant effects on the LBP, However, there is significant relationship between social support and the LBP with R2 = 0.131. This research enables each hospital's Occupational Safety and Health department and agencies affiliated with the Malaysian Ministry of Health to foresee and comprehend the need for its healthcare professionals to work in an optimal environment.